Do jogo role-playing game ao ensino em saúde: uma abordagem transdisciplinar para o enfrentamento da obesidade e sobrepeso - Eltchechem, Bruno Da Luz (2021)
This research aims to understand how the different areas of knowledge can complement and interact in a transdisciplinary way, to address and formulate the complex character of obesity. Over the years, weight gain in young people and children has been saw as a sign of excellence in health and development. However, the number of individuals in contemporary society with obesity and overweight is increasing, to the point that this pathology is known as an epidemic disease with the potential to cause drastic damage to health. Thus, there is a need for greater attention to obesity, as it is a multifactorial disease, both in its origin and in its development. Therefore, facing this reality through researches related to this theme, which address the aggravating factors and/or the risks associated with it, can configure an attempt to reverse, even if a little, the current unfavorable reality and statistics in which we live. This work is qualitative research with participant-observation and will feature a pre-game didactic intervention with the purpose of grounding and substantiating the theme to the participants, which, added to previous knowledge, will provide the necessary input for the development and application of the product of this research. , the Role playing-game (RPG). The transdisciplinary approach given to obesity in the development and application of the game, should integrate the areas of knowledge, to promote collaborative participation, in order to diversify the construction of knowledge, becoming a facilitating learning tool, capable of helping to expand the conceptions.